Bone mineralization in Brazilian adolescents: The years of maximum bone mass incorporation - Silva, Carla C. [UNESP]; Goldberg, Tamara Beres Lederer [UNESP]; Teixeira, Altamir Santos [UNESP]; Dalmas, José C. [UNESP] (My University, 2007)
Puberty is the fundamental period for bone mass (BM) acquisition. In this period mineralization is found to increase with levels of high bone formation. The critical years of intense bone anabolism deserve special attention, as adequate gain could minimize fracture risk in later years. The objective of this work was to study bone mineral content (BMC) and bone mineral density (BMD) in male adolescents with age bracket and maturation level. Sixty-one healthy male 10 to 19 year-olds were evaluated for calcium intake, weight, stature, BMI, puberty stage and BMC and BMD in the lumbar spine and femur. BM was measured by bone densitometry (DXA). Calcium intake was calculated by recording 3 days diet. Puberty stage was defined as per Tanner. Descriptive statistics was used with means and standard deviations, linear correlation, and analysis of variance for comparison between age groups, and the Tukey test (p<0.05). Linear correlation was positive and indicated body weight as the main correlation variable with BMD in both studied locations (p<0.01). BMC and BMD increased with age, differences were significant from 14 to 15 years, and when adolescents reached Tanner stage G4. These results showed a pronounced increase in bone mineralization, with the years after 14 to 15 being critical for BM acquisition in Brazilian adolescents.
Keywords: Adolescence; Bone mass; Bone mineral density; Calcium intake; Pubertal events; adolescent; adult; age distribution; body mass; bone density; bone mineralization; Brazil; calcium intake; child; femur; human; lumbar vertebra; male; photon absorptiometry; physiology; puberty; radiography; reference value; Absorptiometry, Photon; Adolescent; Adult; Age Distribution; Body Mass Index; Bone Density; Calcification, Physiologic; Calcium, Dietary; Child; Femur; Humans; Lumbar Vertebrae; Male; Puberty; Reference Values